The Role of Environmental Graphic in the Identification of Urban Public Spaces - Hanieh Eshaghzadeh Torbati (Salehan Institute of Higher Education, 2018)
Today one of the important spaces in cities is the public spaces that, according to their classification and specifications, there is no limit to the use of different groups of people, and due to the presence of all type of people in these spaces, attention to identifying is of paramount importance. Environmental graphic is one of the useful tools to design the spaces and create identity. Of course we know that urban identity is based on the relationship and coordination of various branches of art and science such as psychology, sociology, economics, traffic, landscaping, urbanization, architecture, graphic design and so on. Although, as an interdisciplinary topic, it can be said that this branch of graphic can affect urban identity reformation, given its potentials. In this paper we attempt to study about this topic through applied descriptive-analytic method and to consider the position and importance of environmental graphic in create identity for urban public spaces, using required parameters analyze and definition by library method. Considering the space constructed in city without notice to identity, we analyze this important that if there is public space made with environmental graphic, how it creates an identity.